Overexpression of the ubiquitin‐editing enzyme A20 in the brain lesions of Multiple Sclerosis patients: moving from systemic to central nervous system inflammation. (18th November 2020) - Perga, Simona; Montarolo, Francesca; Martire, Serena; Bonaldo, Brigitta; Bono, Gabriele; Bertolo, Jessica; Magliozzi, Roberta; Bertolotto, Antonio
Abstract: Multiple Sclerosis (MS) is a chronic demyelinating disease of the central nervous system (CNS) in which inflammation plays a key pathological role. Recent evidences showed that systemic inflammation induces increasing cell infiltration within meninges and perivascular spaces in the brain parenchyma, triggering resident microglial and astrocytic activation. The anti‐inflammatory enzyme A20, also named TNF associated protein 3 (TNFAIP3), is considered a central gatekeeper in inflammation and peripheral immune system regulation through the inhibition of NF‐kB. The TNFAIP3 locus is genetically associated to MS and its transcripts is downregulated in blood cells in treatment‐naïve MS patients. Recently, several evidences in mouse models have led to hypothesize a function of A20 also in the CNS. Thus, here we aimed to unveil a possible contribution of A20 to the CNS human MS pathology. By immunohistochemistry/immunofluorescence and biomolecular techniques on post‐mortem brain tissue blocks obtained from control cases (CC) and progressive MS cases, we demonstrated that A20 is present in CC brain tissues in both white matter (WM) regions, mainly in few parenchymal astrocytes, and in grey matter (GM) areas, in some neuronal populations. Conversely, in MS brain tissues, we observed increased expression of A20 by perivascular infiltrating macrophages, resident‐activated astrocytes, and microglia in all the active and chronic active WM lesions. A20 was highly expressed also in the majority of active cortical lesions compared to the neighboring areas of normal‐appearing grey matter (NAGM) and control GM, particularly by activated astrocytes. We demonstrated increased A20 expression in the active MS plaques, particularly in macrophages and resident astrocytes, suggesting a key role of this molecule in chronic inflammation. Abstract : The anti‐inflammatory enzyme A20, codified by the TNFAIP3 gene, is genetically associated to MS and its transcripts is down‐regulated in blood cells of treatment‐naïve MS patients. By immunohistochemistry/immunofluorescence and biomolecular techniques on post‐mortem brain tissues of progressive MS cases, we observed an increased expression of A20 in the active and chronic active white matter lesions and in the active cortical lesions, particularly in activated astrocytes. Our results suggest a key role of A20 also in chronic inflammation of the central nervous system.